Pengaruh Literasi Keuangan Literasi Pajak dan Literasi Digital Terhadap Minat Investasi Mahasiswa Universitas Mercu Buana Yogyakarta di Pasar Modal - Kumanireng, Ignasia Helena Waleng; Bayu Utomo, Rochmad (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2023)
This research was conducted with the aim of determining whether financial literacy, tax literacy and digital literacy owned by students of Universitas Mercu Buana Yogyakarta have a significant effect on investment interest in the capital market. The variables used in this study are financial literacy, tax literacy and digital literacy as independent variables and investment interest as dependent variables. The research method used is quantitative research method. The data source used is primary data by distributing questionnaires. The population in the study is all students of Universitas Mercu Buana Yogyakarta who invest in the Capital Market which is not yet known in number. The number of samples in this study was 108 respondents obtained using the formula Hair et al. The data analysis technique used in this study is multiple linear regression analysis. The results showed that financial literacy and digital literacy positively affect the investment interest of Universitas Mercu Buana Yogyakarta students in the Capital Market. Meanwhile, tax literacy does not have a significant effect on the investment interest of Universitas Mercu Buana Yogyakarta students in the Capital Market.